Factors Affecting Capital Structure in Manufacturing Companies Go-Public in Indonesia Stock Exchange in The Year 2011-2013 - Riswan RISWAN; Nina Permata Sari (Jurnal Akuntansi dan Keuangan, 2015)
The purpose of this study was to examine the effect only Profitability, growth in sales, taxes, asset structure, dividends, company size and business risks to the Capital Structure Manufacturing Company In Indonesia Stock Exchange Period 2011-2013. Companies that were sampled 31 companies and the number of observations made during 2011-2013 was 93 items observation. Methods of data analysis in this study using multiple linear regression. Based on the calculation results obtained values of R square of 0.487 which means that48.70% of capital structure is influenced by the variable profitability, sales growth, taxation, asset structure, dividends, company size and business risks. While the remaining 51.30% is influenced by other variables not examined in this study. Based on calculations by the statistical test t of the entire independent variables that exist only variable profitability, asset structure, company size and business risks singnifikan effect on Capital Structure. While sales growth variable, taxes, and dividends do not have a significant effect on the capital structure.